DEMOGRAPHIC DATA OF COMPANION ANIMALS TREATED IN AN OPHTHALMOLOGY CLINIC AND OF THEIR CARETAKERS - Hugues H., Beatriz (2014)
Demographic data related to companion animals (n=610) assisted in the ophthalmology veterinary clinic in Havana during 2012 and of their caretakers (n=529) is described. Retrospective data were obtained from clinical records. The dogs were the most frequent species (68%), followed by cats (22%), hamster (5%) and turtles (4%). Dogs were mainly female (62%), between 1 to 5 years old (35%), and the most representative breeds were undefined crossbreds (37%), Pekingese (27%) and Cocker Spaniel (11%). The caretakers were mostly women (68%) between 31 to 50 years old (55%), with high school level of education (90%), workers (68%), living with other family members (92%) and the house was usually in districts close to the clinic. The main reason for keeping pets, especially dogs and cats was affection (85 and 60% respectively).